Strategies of the Pandeglang Regency Government in Enhancing the Tourism Potential of Cikoromoy Natural Springs in 2024: (Strategies of the Pandeglang Regency Government in Enhancing the Tourism Potential of Cikoromoy Natural Springs in 2024) - Fikri Fakhrial Amin; Nandang Alamsah Deliarnoor; Jajang Sutisna (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Penelitian ini menganalisis strategi Pemerintah Kabupaten Pandeglang, khususnya Dinas Pariwisata dan Kebudayaan, dalam pengembangan potensi pariwisata Pemandian Alam Cikoromoy tahun 2024 dengan pendekatan kualitatif deskriptif. Analisis dilakukan menggunakan tiga dimensi manajemen strategi David, yaitu strategi, penerapan, dan penilaian strategi. Data diperoleh melalui wawancara, studi pustaka, serta informasi dari pengelola, pengunjung, dan masyarakat. Hasil penelitian menunjukkan bahwa perumusan strategi telah mengacu pada dokumen perencanaan daerah dan pusat, namun belum komprehensif dan partisipatif. Penerapan strategi belum efektif karena keterbatasan anggaran, sumber daya manusia, fasilitas, serta belum adanya pengembangan produk wisata baru. Penilaian strategi telah dilakukan secara rutin, tetapi belum menjadi dasar perbaikan yang berkelanjutan. Penelitian ini menyimpulkan bahwa strategi pengembangan Pemandian Alam Cikoromoy belum berjalan optimal dan memerlukan pembenahan menyeluruh pada aspek perumusan, penerapan, dan penilaian strategi agar pembangunan pariwisata daerah dapat tercapai secara efektif dan berkelanjutan. Abstract This study analyzes the strategy of the Pandeglang Regency Government, particularly the Department of Tourism and Culture, in developing the tourism potential of Cikoromoy Natural Bath in 2024 using a descriptive qualitative approach. The analysis is based on three dimensions of strategic management proposed by David, namely strategy formulation, strategy implementation, and strategy evaluation. Data were collected through interviews, literature review, and information from managers, visitors, and the local community. The results indicate that strategy formulation has referred to regional and national planning documents; however, it has not been comprehensive and participatory. Strategy implementation has not been effective due to limited budgets, human resources, facilities, and the absence of new tourism product development. Strategy evaluation has been conducted regularly, but it has not yet served as a basis for sustainable improvement. This study concludes that the development strategy of Cikoromoy Natural Bath has not been optimally implemented and requires comprehensive improvements in strategy formulation, implementation, and evaluation to achieve effective and sustainable regional tourism development.